Female Suicide and the Concept of the Midlife Crisis - Andrew J. Oswald; Ahmed Tohamy (Institute of Labor Economics (IZA), 2017)
The idea that humans especially females are prone to some form of 'midlife crisis' has typically been viewed with extreme skepticism by social scientists. We point out the potential equivalence between an age U-shape in a new well-being literature and a matching hill-shape in especially female suicide risk (evident in 28 countries and visible in the United States even 30 years ago). This concordance between two currently separate kinds of evidence, including a result on non-human primates, is apparently not known to many researchers or public commentators. It may be necessary to reconsider traditional thinking on the midlife crisis.
Keywords: I12; I31; 330; happiness; aging; suicide; well-being; GHQ; mental-health; depression; life-course